Organocatalytic highly enantioselective conjugate addition of aldehydes to alkylidine malonates - Zhao, G; Vesely, J; Sun, J; Christensen, K; Bonneau, C; Cordova, A (2008)
The first highly enantioselective, direct organocatalytic conjugate addition of unmodified aldehydes to alkylidinemalonates is presented. The reaction gives access to β-formyl-substituted malonates and highly functionalized lactones with up to 14:1 dr and generally 94 to >99% ee. © 2008 Wiley-VCH Verlag GmbH and Co. KGaA.